Money and Inflation in the Islamic Republic of Iran - Bonato, Leo (IMF Working Papers; Working Paper ;, 2007)
This paper looks at the determinants of inflation in Iran. Unlike the traditional estimates of the demand function for real money balances, the approach followed here focuses on the relationship between nominal variables and inflation. The model estimates are used to address the questions raised by the decline in inflation that occurred up to the first half of 2006, looking at the structural stability of the estimated relationships and the ability of the model to predict inflation at the end of the sample. The estimates confirm the strong relationship between money and inflation when M1 is used, with no evidence of a structural change.